Polityka narodowościowa i kolonialna Związku Radzieckiego w ujęciu historiografii amerykańskiej: Nationality and Colonial Policies of the Soviet Union in U.S. Historiography - Puchalski, Piotr (Przegląd Wschodnioeuropejski, 2019)
Changes in American interpretations of Soviet nationality policies have reflected broader shifts in U.S. historiography of the former U.S.S.R. Notwithstanding pro-Soviet apologists, U.S. scholars initially viewed the Soviet expansion into neighboring non-Russian lands as forced and integral to the emergence of the Soviet “party-state.” In effect, the Soviet rule, in particular outside of ethnic Russia, was perceived as brutal and often colonial in nature. The fall of the Soviet empire and resulting political relaxation, however, presented a turning point for the field, ushering in the so-called “archival revolution.” Consequently, the topic literature increasingly interpreted Soviet policies no longer as necessarily colonial but instead responsible for generating modern nationalities, or at least national categories. At the same time, the Soviet-era ideological divisions among U.S. scholars have not completely disappeared, while the more recent postmodern tendencies have affected the field in both positive and negative ways. Theoretical approaches that encourage comparative analysis and the deconstruction of analytical categories are used productively to maintain critical distance but also carry the risk of moral relativism.